The effect of biochar on enhancing soil fertility, mitigating soil salinity and promoting plant growth: a review - Abdul Hallim Majidi (EQA)
Biochar (BC) is a widely recognized soil amendment, produced by pyrolysis from different biomass, its potential is determined through pyrolysis temperature and feedstock material. Biochar produced at maximum temperatures (> 500 ℃) increased bulk density and porosity to greater levels. It is produced at minimum pyrolytic temperature (< 500 ℃) had more influence on bacterial diversity, and the type of organic resources can affect soil bulk density. Application of BC to soil can enhance its quality and reduce the effects of salt, drought, and contamination as well as climate change. The addition of biochar to soil improves its physical and chemical properties, like porosity, moisture content, and water-holding capacity. BC, can enhance the fertility of soil, improve the retention of nutrients, and decrease the salinity of the soil, all of which can increase crop yields. Moreover, biochar could capture C in the soil and is an effective method to mitigate climate change, improve soil management, and promote agricultural sustainability in Semi-arid and Arid areas.